Recognition of Non-Formal and Informal Learning: Social Partnership Aspect - Laužackas, Rimantas; Kaminskienė, Lina (Acta Paedagogica Vilnensia, 2004)
The article focuses on the problem of the relations and cooperation of the worlds of education and labour. Today’s vocational education and training system (VET ) cannot function separately without a close link to the labour market. Cooperation with employers, the so-called social-economical partners, helps the VET system to keep the balance between the supply and demand of competencies and qualifications necessary in the present world. This cooperation now extends the boundaries of the formal educational system, thus, turning to the need of assessing and validating non-formal and informal learning. The article analyses three main levels (decision making level, learning paths level and learning process level) of the cooperation between social partners and VET institutions, also giving an overview of experience of recognising non-formal and informal learning in France and the situation in Lithuania. The analysis brings important conclusions related to the problems (institutional and methodological) in assessing and validating non-formal and informal learning and the role of social-economical partners in VET.